1997
DOI: 10.1007/s004310050559
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal seizures

Abstract: The newborn brain is particularly vulnerable to seizures which are associated with poor neurodevelopmental outcome. The clinical manifestations of seizures in infants differ from those seen in older children and adults. The problem of electro-clinical dissociation, where there is no temporal correspondence between electrical paroxysms and repetitive stereotyped motor phenomena, is common in the newborn. There is at present very little information on which clinicians can base a rational decision about treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 30 publications
0
36
0
3
Order By: Relevance
“…Seizures occur in 6%-13% of low birth weight infants and 1-2 per 1000 infants born at term [2]. Although changes in heartbeat timing have been described during neonatal seizures [1]- [4], they are much neglected in automatic seizure detection research.…”
Section: Introductionmentioning
confidence: 99%
“…Seizures occur in 6%-13% of low birth weight infants and 1-2 per 1000 infants born at term [2]. Although changes in heartbeat timing have been described during neonatal seizures [1]- [4], they are much neglected in automatic seizure detection research.…”
Section: Introductionmentioning
confidence: 99%
“…15 In our study, metabolic disturbances were found in 11 neonates (28.95%), mainly resulted in hypocalcemia. Rennie 16 and Pressler 17 stated that hypocalcemiahypomagnecemia as the etiology of 4-22% of cases. Intracranial hemorrhage was diagnosed as the etiology of neonatal seizures in 7 cases (18.42%).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that immature neurons differ from mature neurons in their reactions to pathological conditions (Rennie, 1997;Olney et al, 2004). To understand which cellular responses to trauma are different and which are similar, immature and mature neurons must be analyzed in comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Since learning and motor deficits are often a long-term outcome of neonatal brain injury (Rennie, 1997;Volpe, 2001;Ferriero, 2004), it is vital to define how excitotoxic compounds lead to these defects. AMPA/KA-R activation has been shown to regulate motility of filopodia in growing axons of hippocampal cultures (Chang and De Camilli, 2001), suggesting that AMPA-Rs are involved in controlling axonal extension.…”
Section: Sublethal Activation Of Ampa-rs Causes Neuritic Degenerationmentioning
confidence: 99%
See 1 more Smart Citation